Mixed neuroendocrine carcinoma and hepatocellular carcinoma in the liver. Issue 1 (22nd December 2022) - Tanaka, Haruka; Sugo, Hiroyuki; Iwanaga, Naoki; Machida, Michio; Watanobe, Ikuo; Okubo, Hironao; Hotchi, Shiori; Ogura, Kanako
Abstract: Background: Mixed neuroendocrine carcinoma (NEC) and hepatocellular carcinoma (HCC) is extremely rare, thus radiological features have not been fully clarified. Case: A male patient (age: 70 years) visited our hospital due to a tumor in the liver. Examination using contrast‐enhanced computed tomography (CT) revealed a tumor (diameter: 5.0 cm) in hepatic segment 5, with early enhancement of the peripheral area and slight internal heterogeneous enhancement in the arterial and delayed phases, respectively. F‐18 fluorodeoxyglucose (FDG)‐positron emission tomography (PET)/CT revealed intratumoral heterogeneity, characterized by increased uptake (standardized uptake value, 12.10) in the corresponding low‐density area detected using enhanced CT relative to the surrounding areas of the tumor. On magnetic resonance imaging, diffusion‐weighted imaging also showed high intensity in the corresponding low‐density area detected using CT. Preoperatively, the patient was diagnosed with HCC and underwent anterior sectionectomy. Pathological findings revealed both HCC and NEC components, and the patient was diagnosed with mixed NEC and HCC. Comparison of component distribution with FDG‐PET/CT revealed an increased uptake area was congruent with the NEC component in the tumor. Conclusion: In this case, the difference in tumor components affected the uptake in FDG‐PET/CT. Such heterogeneous uptake with an enhanced spot may be useful for suspecting the presence of mixed NEC and HCC in patients with atypical HCC.